Molecular Dynamics Simulation of Various Bioactive Compounds of Red Betel (Piper crocatum) as Anti-Inflammatory Drug-Like Candidates in Rheumatoid Arthritis Treatment - Maslikah, Siti Imroatul; Putra, Wira Eka (Trends in Sciences, 2024)
Joint inflammation and damage can be caused by rheumatoid arthritis (RA), a systemic autoimmune disorder. Long-term RA affects the joints, causing pain, edema, and stiffness. Several studies have revealed that the exact origin of RA is still unidentified, but inherited disorder and external factors may contribute to the inflammatory condition. The incidence of RA is mostly caused by uncontrolled-production of pro-inflammatory cytokines under nuclear factor-kappa B (NF-κB) overexpression condition. The nuclear factor-kappa B plays an important role in inflammatory T cell activation, differentiation, and effector function. Therefore, the inhibition of NF-κB can be a strategy to reduce the adverse effects or incidence of RA. Red betel is a perennial herb native to Indonesia that is widely used by conventional healers. Many reports show that red betel leaf extracts contain several critical bioactive compounds such as Apigenin, Luteolin, Hydroxychavicol, Eugenol, and Chavibetol. This present study aims to evaluate and predict the therapeutic potential of those compounds as medication that reduce inflammation against RA by disturbing and inactivating the NF-κB molecular interaction. The LC-MS chromatography was used to evaluate the chemical contents of red betel leaves. Furthermore, in silico study, the 3D structure of the active compounds of red betel leaves is obtained from PubChem web server, while NF-κB is obtained from Protein Data Bank (PDB) website. Molecular docking was used to screen the potential compounds compared to aspirin as control. As a result, 2 compounds including Apigenin and Luteolin have smaller bond affinity values, −6.3 and −6.0 kcal/mol, respectively compared to aspirin. Based on molecular dynamics (MD) simulation, the root-mean-square deviation (RMSD) value of protein-ligand complexes have the similar pattern over 1000/ps except the NF-κB-Chavibetol complex which has an unstable pattern. On the other hand, the total energy of the protein-ligand complexes have similar average number of −1.69 kJ/mol. The simulation indicates the ligands have constant binding energy to the protein. Furthermore, numerous pharmacokinetic properties of compounds including absorption, distribution, metabolism, excretion and toxicity are exponentially greater than the control drugs. Finally, red betel active compounds can be used as alternative candidates of RA therapy medication. HIGHLIGHTS Rheumatoid arthritis, a systemic autoimmune condition, damages joints. Long-term RA causes joint discomfort, swelling, and stiffness. The identified flavonoids from red betel leaf extract include flavonone, isoflavone, auron, catechin, anthocyanidin, and chalcone. Apigenin, chavibetol, eugenol, hydroxychavicol, and luteolin, the active chemicals found in red betel, have the potential to serve as NF-B inhibitors, making them potentially useful in the treatment of rheumatoid arthritis. GRAPHICAL ABSTRACT